Застосування Тіоцетаму в комплексній терапії бойової контузії головного мозку - Бєленічев, Ігор Федорович; Нерянов, К. Ю.; Черній, В. І.; Середа, Д. А.; Кучеренко, Людмила Іванівна; Дерев'янко, Наталя Вікторівна; Кандибей, Костянтин Іванович; Bielenichev, I. F.; Nerianov, K. Yu.; Chernii, V. I.; Sereda, D. A.; Kucherenko, L. I.; et al. (Запорізький державний медико-фармацевтичний університет, 2023)
Мета роботи – вивчення застосування Тіоцетаму в комплексній терапії бойової контузії головного мозку та оцінювання його терапевтичної дії в пацієнтів із легкою та середньотяжкою закритою бойовою черепно-мозковою травмою порівняно з базисною терапією. Матеріали та методи. Обстежили 79 хворих із легкою та середньотяжкою закритою бойовою черепно-мозковою травмою. У 76 осіб ЧМТ спричинена мінно-вибуховою травмою; діагностували струс головного мозку, забій головного мозку легкого ступеня, перелом склепіння черепа. Хворі надходили до відділення в гострому періоді. Під час дослідження використано клінічні та функціональні методи оцінювання стану центральної нервової системи. Проаналізовано результати комплексного лікування. Результати. Застосування Тіоцетаму не спричиняло підвищення збудливості, нервозності, порушення сну в пацієнтів. Проаналізували вегетативну реактивність після лікування Тіоцетамом. Встановили, що показник нормальної вегетативної реактивності збільшився до 60 %, а в контрольній групі – до 42 %. Показники пацієнтів із підвищеною вегетативною реакцією зменшилися з 42,8 % до 17,9 %, у контрольній групі – з 38,5 % до 23,1 %. Позитивний клінічний ефект в основній групі пацієнтів, які отримували Тіоцетам, спостерігали у 94 % випадків у перші 5 днів. У контрольній групі позитивний клінічний ефект визначили в 76 % випадків. Поліпшення виявили і в клінічній сфері, і за показниками вегетативної реактивності ЕЕГ, шкали дослідження когнітивних функцій MMSE. The aim of this study is to investigate the utilization of Thiocetam as part of a comprehensive treatment approach for combat-related cerebral contusion and to assess the therapeutic effects of Thiocetam in patients with mild and moderate closed combat craniocerebral trauma in comparison to standard basic therapy. Materials and methods. 79 patients with mild and moderate closed combat craniocerebral trauma were examined. Among them, 76 patients experienced craniocerebral trauma due to an explosive blast injury, which included conditions such as brain concussion, mild cerebral contusion, and cranial vault fractures. All patients were admitted to the department during the acute period of their injuries. During the study, various clinical and functional methods were employed to assess the condition of the central nervous system. These methods were used to evaluate the effects of the complex treatment administered to the patients. Results. The administration of Thiocetam to the patients did not result in an increase in excitability, nervousness, or sleep disturbances. Furthermore, the examination of autonomic reactivity following Thiocetam treatment revealed that the indicator of normal autonomic reactivity increased to 60 % in the treated group, whereas it only increased to 42 % in the control group. Additionally, the patients with initially heightened vegetative reactions experienced a decrease from 42.8 % to 17.9 % in the treated group, while the control group saw a decrease from 38.5 % to 23.1 %. In terms of clinical outcomes, a positive effect was observed in 94 % of patients in the Thiocetam-treated group within the first 5 days. In comparison, the control group showed a positive clinical effect in 76 % of cases. This improvement was evident both in the clinical field and based on indicators of autonomic reactivity in EEG data, as well as cognitive function assessed by the MMSE cognitive function test scale.
The use of Thiocetam in the complex therapy of combat-related brain contusion
Бєленічев І. Ф. - ORCID ID: 0000-0003-1273-5314; Кучеренко Л. І. - ORCID ID: 0000-0003-2229-0232; Дерев’янко Н. В. - ORCID ID: 0000-0003-3349-867X; Кандибей К. І. - ORCID ID: 0000-0001-7131-2704.
Keywords: ноотропні засоби; травми головного мозку; оксидативний стрес; нейропротекторні засоби; контузії; когнітивні функції; nootropic agents; brain injuries; oxidative stress; neuroprotective agents; contusions; cognitive function